Can first-trimester aspartate aminotransferase/platelet ratio index score predict intrahepatic cholestasis of pregnancy? - Gok, Koray; Takmaz, Taha; Kose, Osman; Tuten, Nevin; Acikgoz, Abdullah Serdar; Bostanci, Mehmet Suhha; Ozden, Selcuk (My University, 2022)
The study aimed to investigate the effectiveness of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and platelet values in predicting intrahepatic cholestasis of pregnancy (ICP) in the first trimester, together with the aspartate aminotransferase/platelet ratio index (APRI) score.

This study consisted of a patient group diagnosed with ICP (n=49) and a control group (n=62). Laboratory tests of both groups were analyzed retrospectively.

The first-trimester APRI score and AST and ALT values were found to be statistically significantly higher than those of the control group. The platelet value was found to be statistically significantly lower in the study group, even though it was within the normal reference range.

The first-trimester APRI score was found to be effective in predicting ICP. In addition, the first-trimester AST, ALT, and platelet values were found to be effective in predicting ICP diagnosed in the third trimester even though if not as much as the APRI score.
Keywords: APRI score; intrahepatic cholestasis; prediction; pregnancy